Green Investment or Greenwashing? Foreign Investment in Indonesia’s Renewable Energy Sector - Prahara, Pandu; Siagian, Rhea; Yossi (LIBERATICA, 2025)
This article critically examines the legal implications of greenwashing and the lack of Environmental, Social, and Governance (ESG) accountability in foreign-funded renewable energy investments in Indonesia. While green investment is promoted as part of the global transition toward sustainability, many projects in Indonesia have raised concerns due to aggressive land acquisition, lack of community consent, and misleading ESG reporting. This research applies a socio-legal juridical method by combining normative legal analysis with empirical data obtained from interviews and field documentation in East Java and South Sulawesi. The findings reveal significant regulatory gaps that allow companies to misuse ESG narratives for image-building purposes while neglecting environmental and social responsibilities. The study also highlights the absence of strong enforcement mechanisms and community access to justice, which creates a legal vacuum and facilitates systemic greenwashing. Therefore, this paper proposes regulatory reform and the adoption of binding ESG standards to strengthen transparency, legal accountability, and community rights in Indonesia’s renewable energy sector.